Tutorship programs: a way of accompanying educational trajectories in Veterinary Medicine (FAVE Sección Ciencias Veterinarias, 2020)
The purpose of this work is to socialize the impact of the Mentoring Program in the educational path of the entrants to the veterinary medicine career at the National University of the Coast. The Mentoring Program dates back to 2010 when, through the career improvement plan, the need to start an accompaniment work aimed at incoming students was established. This program is carried out through the professional work carried out by the Chair of Introduction to Veterinary Medicine, the Career Director and the Educational Guidance Service (S.O.E) of the Faculty of Veterinary Sciences, being the co-responsible for said execution. The constant challenge of the program is to respond to the continuous construction of alternatives that allow students to appropriate the necessary skills to achieve academic success. Taking into account the results, it can be seen that the Tutoring Program is recommended by 98% of the tutors, because it is favorable to the university affiliation processes. The novelty of the program is that it is carried out by advanced students, who after a selection and training process carry out the orientation task.
Keywords: peer tutoring; accompaniment; veterinary medicine; inclusion; universitary entrance